2014
DOI: 10.4102/ajlm.v3i2.199
|View full text |Cite
|
Sign up to set email alerts
|

The impact of SLMTA in improving laboratory quality systems in the Caribbean Region

Abstract: BackgroundPast efforts to improve laboratory quality systems and to achieve accreditation for better patient care in the Caribbean Region have been slow.ObjectiveTo describe the impact of the Strengthening of Laboratory Management Toward Accreditation (SLMTA) training programme and mentorship amongst five clinical laboratories in the Caribbean after 18 months.MethodFive national reference laboratories from four countries participated in the SLMTA programme that incorporated classroom teaching and implementatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 11 publications
0
39
0
Order By: Relevance
“…Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,2931 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus. 1,16,23,24,32,33 In total, these studies included detailed information on SLMTA implementation in 211 laboratories in 18 countries.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Six papers presented experiences from a single laboratory 7,10,17,26,28 or a single hospital, 9 14 presented data from two to 45 laboratories within a single African country, 8, 12,–15,18,–22,25,2931 one discussed activities in two Southeast Asian countries, 23 one covered data from four countries in the Caribbean Region 11 and six had a general or global focus. 1,16,23,24,32,33 In total, these studies included detailed information on SLMTA implementation in 211 laboratories in 18 countries.…”
Section: Resultsmentioning
confidence: 99%
“…One study of SLMTA implementation in the Caribbean Region reported that ‘past laboratory assessments and training did not provide them with a structured roadmap to assist in implementation; as a result, the majority of these laboratories did not initiate the process of QMS development and implementation’. 11 Another reported that ‘prior to the introduction of SLMTA, several trainings and quality improvement initiatives had been implemented in hospitals and laboratories in Ethiopia, but little improvement was noted’. 12 In Botswana, there had been ‘slow progress in implementing QMS’, and authors noted that ‘previous training of healthcare workers has focused on general management topics rather than identifying tangible tasks to bring about change, making the training difficult to apply in the laboratory’.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Several countries have utilised the embedded mentorship model incorporated with SLMTA training, with good results. 11,12,13,14 Our SLMTA training for Cohort II was conducted in a decentralised model rather than in centralised workshops; one study in Cameroon also found decentralised training to be effective. 12 …”
Section: Discussionmentioning
confidence: 99%